DYNAMICS OF LOCAL IMMUNOLOGICAL INDICATORS ACCOMPANIED BY DIFFERENT TYPES OF REACTIVITY OF THE ORGANISM - Yarov, Yu.Yu.; Silenko, Yu.I.; Yeroshenko, G.A.; Shevchenko, K.V.; Grygorenko, A.S. (World of Medicine and Biology, 2023)
The dynamics of local immunity in the oral fluid in patients with generalized periodontitis after surgery accompanied by normo-, hyper- and hyporeactivity of the body. It was revealed that tension of local (lysozyme, -lysine, SIgA, IgA, IgG in the oral fluid) immunity with normalization by the end of observation is typical for patients with generalized periodontitis with normoreactivity of the body after surgery. In case of hyperreactivity the dysfunction of local immunity which is shown by the expressed fluctuations of level of lysozyme, -lysine, secretory IgA, IgA and IgG in oral fluid with their imbalance by the end of supervision is defined. In case of hyporeactivity dysfunction of local immunity is observed that is shown by a later rise and rather low amplitude of changes of the investigated parameters.